2022
DOI: 10.3390/ijerph192114546
|View full text |Cite
|
Sign up to set email alerts
|

The Intertwining of Posttraumatic Stress Symptoms, Alcohol, Tobacco or Nicotine Use, and the COVID-19 Pandemic: A Systematic Review

Abstract: Background: Posttraumatic stress symptoms (PTSSs) and alcohol, tobacco, or nicotine use are frequently associated conditions. The COVID-19 pandemic has been a stressful situation globally and has worsened mental health conditions and addictions in the population. Our systematic review explores the links between PTSSs and (1) alcohol use and (2) tobacco or nicotine use during the COVID-19 pandemic. Methods: We searched the PubMed, PsycINFO, and Web of Science databases for studies published between January 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 56 publications
0
1
1
1
Order By: Relevance
“…Though some personal and behavioural factors were associated with PTSD and/or depression in previous studies (e.g. BMI, tobacco or alcohol use, and PTSD) (Mengin et al, 2022 ; Pericot-Valverde et al, 2018 ; Suliman et al, 2016 ), our study revealed no association between BMI, sports activity, alcohol or tobacco consumption, and PTSD in our population. Only a low level of sports activity was associated with depression, which is already acknowledged in the literature (Pearce et al, 2022 ).…”
Section: Discussioncontrasting
confidence: 85%
“…Though some personal and behavioural factors were associated with PTSD and/or depression in previous studies (e.g. BMI, tobacco or alcohol use, and PTSD) (Mengin et al, 2022 ; Pericot-Valverde et al, 2018 ; Suliman et al, 2016 ), our study revealed no association between BMI, sports activity, alcohol or tobacco consumption, and PTSD in our population. Only a low level of sports activity was associated with depression, which is already acknowledged in the literature (Pearce et al, 2022 ).…”
Section: Discussioncontrasting
confidence: 85%
“…Reviews have identified an association between cannabis use and PTSD (100, 101) and investigated the potential for therapeutic use (102)(103)(104). Reviews have also identified an association between tobacco use and PTSD (105)(106)(107)(108)(109), with one meta-analysis by van den Berk-Clark et al (109) finding a strong association (OR 2.13) for unadjusted studies and a weak association (OR 1.22) for a single adjusted study. The evidence for e-cigarette use is very limited (36).…”
Section: Post-traumatic Stress Disordermentioning
confidence: 99%
“…Загалом прояви ПТСР спостерігаються у 1-3% всього населення (у жінок приблизно у 1,5 раза частіше), а окремі компоненти цього розладу -у 5-15% населення. Симптоми ПТСР часто супроводжуються вживанням алкоголю, тютюну чи нікотину [9]. Схильність до алкоголю може бути зумовлена або неадекватним способом впоратися з ПТСР, або вразливістю, наприклад, за умов пандемії COVID-19.…”
Section: вступunclassified